Quantification of Human DNA from Mosquito Blood Meals by Real-Time PCR Technique - Khuannet, Phatsara; Mahacharoen, Thiti; Yanatatsaneejit, Pattamawadee (Suan Dusit Graduate School Academic Journal, 2022)
This research aimed to estimate the time; 0, 24, 48 and 72 hours that elapsed since feeding from the degree of human DNA digestion in mosquitoes blood meal by Real-Time PCR technique. The experimental research was performed using QuantStudio™ 6 Flex Real-Time PCR System to quantitate the blood’s human DNA by primers CADM1 (121, 229 and 397 bp). Samples in the experiment were Aedes aegypti, Aedes albopictus and Culex quinguefasciatus. The statistical analysis and hypotheses testing were conducted with General Linear Model. The results showed that 1) The DNA concentrations of three mosquito species at different time after feeding were significantly different at the statistical significance level of 0.05 (F = 13.906, p value= 0.000) 2) The DNA concentrations of three mosquito species were also significantly different at the statistical significance level of 0.05 (F=4.623, p value=0.018). 3) The analysis of the quality of remaining DNA revealed that it can increase in any period of time. In conclusion, the amounts of DNA decreased gradually over time and the mosquito species had different remaining DNA. The acquired DNA had quality enough for further forensic examination. It can track down persons who were related to crime scene and limit of the number of suspects resulting in judicial process rapidly, correctly and reliably. Besides, it can be effective evidence for analysis.